Thrombophilic Risk Factors in Patients with Central Retinal Vein Occlusion - Marcucci, Rossella; Bertini, Laura; Giusti, Betti; Brunelli, Tamara; Fedi, Sandra; Cellai, Anna Paola; Poli, Daniela; Pepe, Guglielmina; Abbate, Rosanna; Prisco, Domenico (Thrombosis and Haemostasis, 2001)
Few and contrasting data are available on the prevalence of hemostatic risk factors in patients with central retinal vein occlusion (CRVO). Aim of this study was to investigate the metabolic and inherited risk factors for venous thrombosis in 100 CRVO patients (age: 59 yrs; range 18-77) and in 100 controls (age: 56 yrs; range 18-84). In patients homocysteine (Hcy) levels were significantly higher than in controls and were affected by the C677T methylenetetrahydrofolate reductase (MTHFR) polymorphism (p <0.001). The prevalences of activated protein C resistance (APCR), factor V Leiden positivity, elevated PAI-1 and Lp(a) levels were significantly higher in patients with respect to controls. At multivariate analysis, only hyperhomocysteinemia (OR 11, 95% CI 3.6-36.2; p <0.0001) and elevated PAI-1 levels (OR 8.9, 95% CI 3.5-41.3; p <0.01), in addition to hypertension (OR 40.5, 95% CI 8.6-188.8; p <0.00001) and hypercholesterolemia (OR 3.1, 95% CI 1.6-20.5; p <0.05), were independent risk factors for CRVO. These data demonstrate a potential role of hemostatic risk factors in the pathophysiology of CRVO.
Keywords: Central retinal vein occlusion; homocysteine; genetic polymorphisms; fibrinolysis; risk factors